Other people's houses how decades of bailouts, captive regulators, and toxic bankers made home mortgages a thrilling business - Taub, Jennifer (Yale University Press, 2014)
Explores the origins of the Savings and Loan crisis of the 1980s and draws parallels with the financial crisis of 2008, arguing that the failure to regulate banks combined with the laxness of regulators contributed to the crises and are problems that still persist today.